Case Report: Long-term maintenance of GnRH-a combined with dienogest for thoracic endometriosis syndrome - Tang, Huimin; Jia, Qiucheng; Chen, Wanying; Wei, Weiwei; Ma, Zongli; Chen, Jiming (Frontiers in Medicine, 2025)
Thoracic endometriosis syndrome is a rare form of endometriosis in which endometrial tissue is thought to migrate to the lungs and, with the onset of menstruation, the ectopic foci bleed, causing a range of pulmonary manifestations. In this paper we have collected the clinical data of two patients with thoracic endometriosis syndrome, both of whom presented with haemoptysis as the first symptom and had a history of endometriosis. After 6 courses of treatment with gonadotropin-releasing hormone analogues followed by maintenance treatment with dienogest, the patients’ haemoptysis symptoms were relieved, the CT lesions in the lungs were significantly resorbed compared with the previous ones, and no recurrence was observed at long-term follow-up.